ANALYSIS OF INTERNAL AND EXTERNAL FACTORS AFFECTING THE BASIC ARABIC LITERACY OF STUDENTS AT PONDOK PESANTREN BUSTANIL INSHAF IN TELUK RENDAH PASAR VILLAGE - Kamilatul Parida; Helty Helty; Neldi Harianto; Helmun Jamil (Yayasan Adra Karima Hubbi, 2026)
This study aims to identify and analyze the internal and external factors affecting students’ basic Arabic literacy at Pondok Pesantren Bustanil Inshaf in Teluk Rendah Pasar Village. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews, participant observation, and documentation using purposive and snowball sampling techniques. The research participants consisted of four students with varying characteristics of literacy difficulty, one Arabic language teacher, and the head of the pondok pesantren (Islamic boarding school). The results showed that internal factors, including high intrinsic motivation, a Madrasah Ibtidaiyah (Islamic Elementary School) background, and consistent independent study habits, supported basic Arabic literacy. Physical fatigue and linguistic difficulties in reading kitab gundul (unvowelized Arabic texts) and memorizing mufrodat (vocabulary) emerged as major barriers. External factors such as an intensive curriculum and morning muhadatsah (conversation) activities facilitated literacy development, whereas inconsistent implementation of the Arabic-speaking ecosystem (bi'ah arabiyah), limited digital infrastructure, and weak institutional collaboration hindered language acquisition. The novelty of this study lies in identifying a sustainable reinforcing cycle between personal motivation and the ecosystem of a rural pondok pesantren. The findings suggest that pondok pesantren should systematically expand mandatory Arabic-speaking zones to strengthen the natural internalization of students’ basic Arabic literacy.